Efeitos da densidade e tempo de espera em frigorífico sobre o bem-estar animal, lesões da pele e qualidade de carne suína - Rocha, Luana Torres da (2023)
One of the most important phases of animal production is the pre-slaughter period, which is a cause of stress to pigs, and can negatively influence the physiological conditions, as well as the meat quality. The objective of this experiment was to evaluate the effects of stocking density and lairage time at the slaughterhouse on the welfare of pigs (stress physiological parameters and animal behaviour), as well as the quality of carcass (skin damage) and pork meat. To this end, a total of 1.858 immunocastrated male pigs, with mean body weight of 144±11 kg, same genetic background (Agroceres-PIC) and originating from farms of similar design, management and distance from the slaughterhouse (50 km), were distributed into an experimental design in randomized blocks aimed at assessing the effects of two stocking densities (0.42 m²/100kg and 0.66 m²/100kg) and two lairage times (2 h and 6 h), which were combined in order to create the following four treatments: 0.42 m² x 2 h, 0.42 m² x 6 h, 0.66 m² x 2 h and 0.66 m² x 6 h. Animals housed at high density conditions (0.42 m²) showed higher skin damage index, as well as a tendency for higher blood cortisol level at slaughter (P < 0.05 and P = 0.08, respectively). Overcrowding influenced the resting of the animals during the last hour of lairage, with a greater number of pigs standing or sitting due to lack of space to lie down. The pigs that were rested for longer time (6 h) showed increased blood hematocrit at slaughter and pHu value (P < 0.05 for both) when compared to those rested for less time (2 h). The results of this study confirm the negative effect of high density and longer time in the slaughterhouse, mainly on exsanguination blood cortisol levels and skin lesion score on pig carcasses.